2013
DOI: 10.1212/wnl.0b013e3182904d59
|View full text |Cite
|
Sign up to set email alerts
|

Effect of duration and age at exposure to the Stroke Belt on incident stroke in adulthood

Abstract: Objective: To assess whether there are differences in the strength of association with incident stroke for specific periods of life in the Stroke Belt (SB).Methods: The risk of stroke was studied in 24,544 black and white stroke-free participants, aged 451, in the Reasons for Geographic and Racial Differences in Stroke study, a national populationbased cohort enrolled [2003][2004][2005][2006][2007]. Incident stroke was defined as first occurrence of stroke over an average 5.8 years of follow-up. Residential hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 31 publications
(32 reference statements)
3
20
0
Order By: Relevance
“…One recent study showed that the risk of stroke was associated with the proportion of residence in stroke belt in adolescence, suggesting the importance of childhood health circumstances in long-term stroke risk. 106 Further studies are needed evaluating risk factors during early in the life. Social efforts are mandatory to control nontraditional risk factors (eg, childhood obesity) and triggering factors (eg, air pollution), whereas control of traditional risk factor could be basically clinic base.…”
Section: Research Needs and Gapsmentioning
confidence: 99%
“…One recent study showed that the risk of stroke was associated with the proportion of residence in stroke belt in adolescence, suggesting the importance of childhood health circumstances in long-term stroke risk. 106 Further studies are needed evaluating risk factors during early in the life. Social efforts are mandatory to control nontraditional risk factors (eg, childhood obesity) and triggering factors (eg, air pollution), whereas control of traditional risk factor could be basically clinic base.…”
Section: Research Needs and Gapsmentioning
confidence: 99%
“…This is likely to contribute to ethnic differences in CVD, as prolonged exposure to hypertension increases cardiovascular risk. 20,21 Ethnic-specific age thresholds to initiate screening may be required to reduce these differences.…”
Section: General Discussion Of Key Findingsmentioning
confidence: 99%
“…by taking into account the duration of exposure to cardiovascular risk factors, thereby taking into account ethnic differences in the age-of-onset of cardiovascular risk factors). 20,21,24 In this study, we used The Netherlands as a European example to show how ethnic groups may differ in the age to initiate CVD risk screening. Earlier work has shown that ethnic differences in cardiovascular risk factors in The Netherlands are comparable to ethnic differences in other countries, although the magnitude of differences may vary between countries.…”
Section: General Discussion Of Key Findingsmentioning
confidence: 99%
“…For example, birthplace has been associated with cardiovascular mortality, 16 , 17 and adolescents who reside in the stroke belt are at an increased risk of stroke in adulthood. 18 Children who reside in neighborhoods that are economically poor and have low levels of education have an increased risk for obesity regardless of their individual characteristics. 19 Alternatively, living in low-poverty neighborhoods and in neighborhoods with reasonable proximity to supermarkets has been associated with less obesity.…”
Section: Sources Of Health Inequitiesmentioning
confidence: 99%